Korelasi antara Keterampilan Generik Sains dan Sikap Ilmiah terhadap Hasil Belajar Peserta Didik pada Materi Sistem Koordinasi di Kelas XI SMA Negeri 2 Tasikmalaya - Romy Faisal Mustofa; Ryan Ardiansyah; Suci Ismiatul Hasanah (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: Various factors can support efforts to improve student learning outcomes, including generic science skills and scientific attitudes. The study aims to determine the correlation between generic science skills and scientific attitudes on student learning outcomes. Methods: This research is a correlational study using a dual paradigm design with two independent variables. The sample was that used was 60 people who came from 11th grade of Science Program. Result: The result of this research is that there is a strong and very significant correlation between generic science skills and scientific attitudes towards learning outcomes. This is supported by the data analysis results, namely a significance value of 0.000 and a correlation coefficient of 0.623. Conclusion: It could be concluded that generic science skills and scientific attitudes contribute to improving student learning outcomes because students who have generic science skills and an excellent scientific attitude will get optimum learning outcomes. Therefore, generic science skills and scientific attitudes that exist in students must continue to be trained and developed.